Building the Border: Development of the Chordate Neural Plate Border Region and Its Derivatives - Thawani, Ankita; Groves, Andrew K. (Frontiers in Physiology, 2020)
The paired cranial sensory organs and peripheral nervous system of vertebrates arise from a thin strip of cells immediately adjacent to the developing neural plate. The neural plate border region comprises progenitors for four key populations of cells: neural plate cells, epidermis, neural crest cells and the cranial placodes. Putative homologues of these neural plate border derivatives can be found in protochordates such as amphioxus and tunicates. In this review, we summarize key signaling pathways and transcription factors that regulate the inductive and patterning events at the neural plate border region that give rise to the neural crest and placodal lineages. Feed-forward and cross-repressive gene regulatory networks driven by signals from Wnt, Fgf, and Bmp signaling primarily dictate the formation of the crest and placodal lineages. We review these studies and discuss the potential of recent advances in spatio-temporal transcriptomic and epigenomic analysis that may allow a mechanistic understanding of how these signaling pathways and their downstream transcriptional casacades regulate the formation of the neural plate border region.